An Indonesian Pregnant Woman with Lung Cancer and Liver Metastasis : A Case Report - Vito Filbert Jayalie; Dimas Priantono; Zulkifli Amin (Indonesian Journal of Cancer, 2018)
Background: Lung cancer in pregnancy is a rare disease compared to other types of cancer. However, special issue should be applied in order to maximize benefit for mother without harming the fetus.Methods: We present a case of 37-year-old, five months pregnant woman who came to the hospital with chief complain of shortness of breath. Later on, she was found to have a stage IV Non-Small Cell Lung Cancer (NSCLC) with adenocarcinoma subtype.Result: This may be the first lung cancer in pregnancy reported in Indonesia. Being a developing country, several challenges emerged before diagnosing patient of having lung cancer.Conclusion: Careful considerations along with multidisciplinary approach are necessary to provide the best care for the patient.